(3cja JLeY LgGR ceHjhJQ ?s Building a p c for dummies - (3TG eHQR , eGQc (B.s; (3eGQc JTGeHQQ(B.s ((3GdbGgQI (B:s (3OGQ GdaGQhb ddfTQ hGdJhRjY(B.,s, 2003)
(3jJfGhd ehVhY GdcJGH cjajI JLejY LgGR ceHjhJQNGU Hc HOd eeG eJGM ai GdeJGLQ (B.s
(3GdJYQa Ydj echfGJ GdceHjhJQ(B.s
Keywords: (3LgGR GdceHjhJQ (B- (3JLejY(B.s